1957
DOI: 10.1080/01621459.1957.10501381
|View full text |Cite
|
Sign up to set email alerts
|

Non-Additivities in a Latin Square Design

Abstract: A brief history of the Latin square design is given. A generalization of the design to the case in which the rows, columns and treatments represented in the experiment are samples from populations of rows, columns and treatments respectively is studied. A possible frame of reference for the interpretation of the experimental results is described.The leads to what is termed a "population model," various population parameters, means and components of variation which are of interest to the experimenter. No assump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1957
1957
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 15 publications
2
27
0
Order By: Relevance
“…Wilk and Kempthorne (80) couched this in relatively easy language and symbolism, presented finite-model expectations of mean squares from which EMS's for the other models can be derived quickly, and concluded that analyses of variance for Latin square designs may overestimate the error term for treatment comparisons and underestimate the component of variance due to treatment main effects. Nevertheless, when both the Latin square and the randomized block designs are reasonable for a proposed experiment, they recommend the former, tho with caution, because its error term for the treatment mean square will usually be too large.…”
Section: Four Basic Articlesmentioning
confidence: 98%
“…Wilk and Kempthorne (80) couched this in relatively easy language and symbolism, presented finite-model expectations of mean squares from which EMS's for the other models can be derived quickly, and concluded that analyses of variance for Latin square designs may overestimate the error term for treatment comparisons and underestimate the component of variance due to treatment main effects. Nevertheless, when both the Latin square and the randomized block designs are reasonable for a proposed experiment, they recommend the former, tho with caution, because its error term for the treatment mean square will usually be too large.…”
Section: Four Basic Articlesmentioning
confidence: 98%
“…Earlier results in the literature on this topic deal with testing for the presence of a subject-treatment interaction (i.e., nonadditivity) by testing for its observable consequences (10,11) or with finding transformations of the data so that subject-treatment additivity appears to hold on the transformed scale (12). Earlier results in the literature on this topic deal with testing for the presence of a subject-treatment interaction (i.e., nonadditivity) by testing for its observable consequences (10,11) or with finding transformations of the data so that subject-treatment additivity appears to hold on the transformed scale (12).…”
Section: Defining Subject-treatment Interactionmentioning
confidence: 99%
“…Wilk and Kempthorne (1957) developed this argument further. In 1957, Kempthorne chaired a six-week I.M.S. Summer Institute on the topic at Boulder, Colorado.…”
Section: A Fixed Finite Population or An Assumption Of Additivity?mentioning
confidence: 99%